2016
DOI: 10.1016/j.aca.2016.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Direct identification of prohibited substances in cosmetics and foodstuffs using ambient ionization on a miniature mass spectrometry system

Abstract: Significantly simplified work flows were developed for rapid analysis of various types of cosmetic and foodstuff samples by employing a miniature mass spectrometry system and ambient ionization methods. A desktop Mini 12 ion trap mass spectrometer was coupled with paper spray ionization, extraction spray ionization and slug-flow microextraction for direct analysis of Sudan Reds, parabens, antibiotics, steroids, bisphenol and plasticizer from raw samples with complex matrices. Limits of detection as low as 5 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 77 publications
(92 reference statements)
0
26
0
Order By: Relevance
“…Reported applications demonstrate the utility of specific ambient MS techniques in this arena, allowing the direct analysis of utilized surface swabs [24], trace residues [41], bulk evidence [42], and highly complex sample matrices [26,43]. Furthermore, implementing automated spectral library searching and chemical identification on said systems can alleviate the need for field-based data interpretation, allowing the use by nontechnical operators [44].…”
Section: A Review Of the 2009 Census For Publicly Funded Forensicmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported applications demonstrate the utility of specific ambient MS techniques in this arena, allowing the direct analysis of utilized surface swabs [24], trace residues [41], bulk evidence [42], and highly complex sample matrices [26,43]. Furthermore, implementing automated spectral library searching and chemical identification on said systems can alleviate the need for field-based data interpretation, allowing the use by nontechnical operators [44].…”
Section: A Review Of the 2009 Census For Publicly Funded Forensicmentioning
confidence: 99%
“…Incorporation of tandem MS data in analyte identification even allows discernment from complex matrices [26,43]. Previous work towards establishing spectral congruence and selectivity compared blind portable MS/MS data to a widely accepted reference library, the 'Wiley Registry of Tandem Mass Spectral Data, MSforID', returning the correct identification for over 30 forensic analytes and evidentiary samples [44].…”
Section: Selectivity Of Analyte Identificationmentioning
confidence: 99%
“…5c) represents an easy means of real time extraction and ionization for MS analysis using lab-scale (Fig. 5d) [66] or miniature mass spectrometers [67]. A liquid-liquid extraction was performed in a nanoESI tube between the biofluid sample and an organic solvent.…”
Section: Future Challenges and Solutionsmentioning
confidence: 99%
“…Furthermore, benzophenone‐1 in nail products was derivatized with N , O ‐bis(trimethylsilyl) trifluoroacetamide, making it amenable to GC–MS analysis . Two simultaneous derivatization and preconcentration approaches have been described for the determination of parabens and cholesterol oxides in shampoo, cream, and lipsticks. Results indicated that good recoveries and high sensitivity were obtained.…”
Section: Sample Preparation Techniquesmentioning
confidence: 99%